'Relieved to be seen'—patient and carer experiences of psychosocial assessment in the emergency department following self-harm: qualitative analysis of 102 free-text survey responses. Issue 5 (23rd May 2021) - Quinlivan, Leah M; Gorman, Louise; Littlewood, Donna L; Monaghan, Elizabeth; Barlow, Steven J; Campbell, Stephen M; Webb, Roger T; Kapur, Navneet
Abstract : Objectives: We sought to explore patient and carer experiences of psychosocial assessments following presentations to hospital after self-harm. Design: Thematic analysis of free-text responses to an open-ended online survey. Setting: Between March and November 2019, we recruited 88 patients (82% women) and 14 carers aged ≥18 years from 16 English mental health trusts, community organisations, and via social media. Results: Psychosocial assessments were experienced as helpful on some occasions but harmful on others. Participants felt better, less suicidal and less likely to repeat self-harm after good-quality compassionate and supportive assessments. However, negative experiences during the assessment pathway were common and, in some cases, contributed to greater distress, less engagement and further self-harm. Participants reported receiving negative and stigmatising comments about their injuries. Others reported that they were refused medical care or an anaesthetic. Stigmatising attitudes among some mental health staff centred on preconceived ideas over self-harm as a 'behavioural issue', inappropriate use of services and psychiatric diagnosis. Conclusion: Our findings highlight important patient experiences that can inform service provision and they demonstrate the value of involving patients/carers throughout the research process. Psychosocial assessments can be beneficial when empathetic and collaborative but less helpful when overly standardised, lacking in compassion and waiting times are unduly long. Patient views are essential to inform practice, particularly given the rapidly changing service context during and after the COVID-19 emergency.